2016
DOI: 10.1016/j.toxlet.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low level lead exposure on associative learning and memory in the rat: Influences of sex and developmental timing of exposure

Abstract: Lead (Pb) exposure during development impairs a variety of cognitive, behavioral and neurochemical processes resulting in deficits in learning, memory, attention, impulsivity and executive function. Numerous studies have attempted to model this effect of Pb in rodents, with the majority of studies focusing on hippocampus-associated spatial learning and memory processes. Using a different paradigm, trace fear conditioning, a process requiring coordinated integration of both the medial prefrontal cortex and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…To more precisely determine the developmental stage when Pb exposure is most important, Anderson et al exposed rats perinatally or postnatally to Pb (0, 150, 375, 750 ppm) and found sex-dependent differences in learning and memory. For example, in a test of memory recall, females were affected more by postnatal exposure to Pb, while males were affected by perinatal exposure [37]. These results may be reflective of the sex-dependent differences in hippocampal transcriptomics this group observed previously [43].…”
Section: Periconceptional Exposures To Lead (Pb)mentioning
confidence: 84%
See 1 more Smart Citation
“…To more precisely determine the developmental stage when Pb exposure is most important, Anderson et al exposed rats perinatally or postnatally to Pb (0, 150, 375, 750 ppm) and found sex-dependent differences in learning and memory. For example, in a test of memory recall, females were affected more by postnatal exposure to Pb, while males were affected by perinatal exposure [37]. These results may be reflective of the sex-dependent differences in hippocampal transcriptomics this group observed previously [43].…”
Section: Periconceptional Exposures To Lead (Pb)mentioning
confidence: 84%
“…After a sharp increase in environmental Pb levels at the end of the 20 th century, stringent United States (U.S.) policies were established to limit the use of Pb in gasoline and paint. While these efforts reduced the risk of exposure to both adults and children [37], early-life exposure to Pb remains a major public health concern. The U.S. Centers for Disease Control and Prevention (CDC) estimates there to be at least 4 million US households where children are exposed to high levels of Pb, primarily through the ingestion of paint [38].…”
Section: Periconceptional Exposures To Lead (Pb)mentioning
confidence: 99%
“…Adverse neurodevelopmental effects of Pb, PS and the combination, as demonstrated in human studies and paralleled in animal models, can be persistent (Anderson et al, 2016; Brubaker et al, 2010; Canfield et al, 2003; Cecil et al, 2008; Cohn et al, 1993; Jett et al, 1997; Lanphear et al, 2005; Li et al, 2016). Findings from this study confirm long-lasting changes in PTHM levels in response to these exposures, as evidenced in FC and HIPP at PND60 with Pb exposure having been discontinued at PND21, with effects differing by sex and by brain region.…”
Section: Discussionmentioning
confidence: 99%
“…All experimental animals were generated in house to reduce outside sources of potential variability. In the PERI exposure group, 50–55 day old LE dams (Envigo Laboratories) and SD dams (Taconic Laboratories) were fed chow (RMH 1000) with or without added Pb acetate (150 ppm or 0 ppm) for 14 days prior to breeding and remained on the same diet through weaning, as previously described (Anderson et al, 2016). Thus, dams were continuously exposed to Pb for approximately 55–60 days.…”
Section: Methodsmentioning
confidence: 99%